1995
DOI: 10.1203/00006450-199505000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor (IGF)-I and IGF-Binding Protein 3 during the First Year in Term and Preterm Infants

Abstract: Plasma IGF-I and IGF-binding protein 3 (IGFBP-3) were determined by radioimmunoassay in term infants (n = 51) at 0, 2,4, 6, and 12 mo and preterm infants (n = 51) at -3 (28.4 wk postconceptional age), -2, -1.5, -1,0,2,4,6,9, and 12 rna from expected term. The effects of gestational age at birth (term or preterm) and study age were determined by repeated measures analysis of variance and Fisher's least squares difference. In preterm infants, IGF-I increased between -3 and 2 mo from 0.75 to 10.4 nM, decreased be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
18
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 24 publications
4
18
3
Order By: Relevance
“…The marked variations in the serum concentrations of IGF-I in the first 18 mo of life will limit its usefulness in the assessment of growth disorder in early life. Contrary to our study, two previous studies reported little variation in the serum IGF-I concentration in the first 1-2 y of life (10,24). The reasons behind this difference in the reported developmental serum growth factors profile are not immediately apparent.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…The marked variations in the serum concentrations of IGF-I in the first 18 mo of life will limit its usefulness in the assessment of growth disorder in early life. Contrary to our study, two previous studies reported little variation in the serum IGF-I concentration in the first 1-2 y of life (10,24). The reasons behind this difference in the reported developmental serum growth factors profile are not immediately apparent.…”
contrasting
confidence: 99%
“…Significant correlation between serum IGF-I and IGFBP-3 concentration was demonstrated in infants from birth to 18 mo of age, consistent with findings from previous studies (10,24,30). A significant increase in serum IGFBP-3 concentration with age was noted in our babies, with a significant rise occurring first at 10 mo of age.…”
supporting
confidence: 91%
“…Newborns show a state of GH resistance, characterized by GH hypersecretion and a low serum IGF-I level (11,12). We observed that this unique profile was more prominent in extremely preterm infants and continued for 3 mo after birth.…”
Section: Discussionmentioning
confidence: 66%
“…GH levels are higher in fetuses and newborns than in children and adults (9). Especially in preterm infants, remarkably high GH and low IGF-I values in serum continue until 1 y of age (10)(11)(12). However, the growth effect of GH does not become apparent until about 18 mo of age, and the clinical significance of GH for perinatal growth has not been well understood (1).…”
mentioning
confidence: 99%
“…AGA infants who are born preterm have increasing serum IGF-I and reach the same values at an age corresponding to term as infants born AGA at term (38). Thus, it seems that weight appropriate for age is as important at birth as during the neonatal period for increasing the serum IGF-I to the levels in AGA infants, and that postnatal growth retardation might be as harmful as intrauterine growth retardation.…”
Section: Discussionmentioning
confidence: 93%